The third Gilmore Girl: a memoir - Bishop, Kelly (Gallery Books, 2024)
A candid and captivating memoir from award-winning and beloved actress Kelly Bishop, spanning her six decades in show business from Broadway to Hollywood with A Chorus Line, Dirty Dancing, Gilmore Girls, and much more.--